2011
DOI: 10.1007/s11604-011-0625-3
|View full text |Cite
|
Sign up to set email alerts
|

Fetal middle cerebral artery peak systolic velocities in a local Indian scenario

Abstract: The results indicate that a local fetus would be anemic even before its MCA-PSV rises to the internationally accepted standard of fetal anemia. Hence, by the time the MCA-PSV value of the local fetus rises to the point where it is deemed severely anemic as per values mentioned in other published literature, it might be too late for intervention and the fetal health as well as life might be at stake. Each geographic locality should therefore develop its own standard values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…After review, 12 studies were retained for the analysis (Figure ). Characteristics of studies included in the meta‐analysis are given in Table and those of studies excluded are given in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“…After review, 12 studies were retained for the analysis (Figure ). Characteristics of studies included in the meta‐analysis are given in Table and those of studies excluded are given in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
“… 7 One retrospective review at a single center from 2000 to 2012 found a transplantation‐free survival from diagnosis to 1 month and 1 year of life to be 35% and 18%, respectively. 8 To our knowledge, the association between hypertrophic cardiomyopathy and elevated MCA PSV has only been described once in the literature 3 with a cause of the hypertrophic cardiomyopathy identified. Specifically, that case was complicated by pre‐existing diabetes mellitus, with an ultimately favorable outcome.…”
Section: Discussionmentioning
confidence: 96%
“…2 An association between fetal hypertrophic cardiomyopathy and elevated MCA PSV has only been described once previously in a pregnancy, which was complicated by pregestational diabetes mellitus with the resolution of both findings postnatally. 3 Here we present two cases in the absence of pre‐existing or gestational diabetes with this association and ultimately poor neonatal outcomes.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations